Japan: Japanese Cultural Promotion for Economic Development (2021)
Soft Power is a strategy used by Japan since the Meiji restoration to position themselves domestically and internationally. Since the 70’s the government incorporates its cultural component as the fundamental tool to influence the actions of international actors. This has allowed the country to project a positive image, transforming its image into economic benefits. The objective of this essay is to analyze the promotion of the Japanese culture as a strategy of Soft Power for the economic development of the country. The paper will discuss Japan´s dedication to cultural and public diplomacy to project its image of a peaceful nation to improve the commercial relationship with its Asian neighbors. The use of Cool Japan for product promotion, tourism, and investment will be discussed later. It will end by examining how the government has reinforced traditional Japanese identity to project itself as an exemplary culture.